Isolation and Identification of a High-Yield Ethyl Caproate-Producing Yeast From Daqu and Optimization of Its Fermentation - Fan, Guangsen; Liu, Pengxiao; Chang, Xu; Yin, Huan; Cheng, Liujie; Teng, Chao; Gong, Yi; Li, Xiuting (Frontiers in Microbiology, 2021)
Baijiu is an important fermented product in China. A yeast named YX3307 that is capable of producing a large amount of ethyl caproate (EC) was isolated from Daqu, a crude fermentation starter for Baijiu. This yeast was identified as Clavispora lusitaniae on the basis of its morphological properties, physiological and biochemical characteristics, and 26S rDNA sequence. Single-factor experiments were conducted to obtain the optimum fermentation conditions for EC production by YX3307. The highest EC yield (62.0 mg/L) from YX3307 was obtained with the following culture conditions: inoculum size 7.5% (v/v), seed cell age 30 h, sorghum hydrolysate medium (SHM) with a sugar content of 10 Brix and an initial pH of 6.0; incubation at 28°C with shaking at 180 rpm for 32 h; addition of 10% (v/v) anhydrous ethanol and 0.04% (v/v) caproic acid at 32 h and 40 h, respectively, static culture at 20°C until 72 h. YX3307 synthesised more EC than ethyl acetate, ethyl lactate, ethyl butyrate, and ethyl octanoate. An intracellular enzyme or cell membrane enzyme was responsible for EC synthesis. YX3307 can produce many flavour compounds that are important for high-quality Baijiu. Thus, it has potential applications in improving the flavour and quality of Baijiu.